Over-expression of NYGGF4 inhibits glucose transport in 3T3-L1 adipocytes via attenuated phosphorylation of IRS-1 and Akt - Zhang Chun-mei; Chen Xiao-hui; Wang Bin; Liu Feng; Chi Xia; Tong Mei-ling; Ni Yu-hui; Chen Rong-hua; Guo Xi-rong (Acta Pharmacologica Sinica, 2016)
Aim: NYGGF4 is a novel gene that is abundantly expressed in the adipose tissue of obese patients. The purpose of this study was to investigate the effects of NYGGF4 on basal and insulin-stimulated glucose uptake in mature 3T3-L1 adipocytes and to understand the underlying mechanisms. Methods: 3T3-L1 preadipocytes transfected with either an empty expression vector (pcDNA3.1Myc/His B) or an NYGGF4 expression vector were differentiated into mature adipocytes. Glucose uptake was determined by measuring 2-deoxy-D-[3H]glucose uptake into the adipocytes. Immunoblotting was performed to detect the translocation of insulin-sensitive glucose transporter 4 (GLUT4). Immunoblotting also was used to measure the phosphorylation and total protein contents of insulin signaling proteins such as the insulin receptor (IR), insulin receptor substrate (IRS)-1, Akt, ERK1/2, p38, and JNK. Results: NYGGF4 over-expression in 3T3-L1 adipocytes reduced insulin-stimulated glucose uptake and impaired insulinstimulated GLUT4 translocation. It also diminished insulin-stimulated tyrosine phosphorylation of IRS-1 and serine phosphorylation of Akt without affecting the phosphorylation of IR, ERK1/2, p38, and JNK. Conclusion: NYGGF4 regulates the functions of IRS-1 and Akt, decreases GLUT4 translocation and reduces glucose uptake in response to insulin. These observations highlight the potential role of NYGGF4 in glucose homeostasis and possibly in the pathogenesis of obesity.